Design and implementation of an adaptive multilevel wireless security system using IoT - Mohammed M. Sultan; Amer T. Saeed; Ahmed M. Sana (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Securing property plays a crucial role in human life. Therefore, an adaptive multilevel wireless security system (ML-WSS) based on the internet of things (IoT) has been proposed to observe and secure a certain place. ML-WSS consists of hardware and software components, such as a set of sensors, Wi-Fi module, and operation and monitoring mobile application (OMM). The OMM application is designed to remotely monitor and control the proposed system through the Internet and by using ThingSpeak cloud as a data store. The proposed scheme is based on dividing the required zone of the place into three regions (levels), low-risk region (LRR) as level-1, moderate-risk region (MRR) level-2, and high-risk region (HRR) as level-3. Each level may contain one or set of sensors, so the number of sensors, their placement, and under which level is labelled is specified according to the security requirements. Several processes are done based on these levels when a breach occurs in the system. Mathematical model and pseudocode were created to illustrate the mechanism of the proposed system. The results show that the proposed system has been implemented successfully and the number of breaches that occurs in level-3 area was reduced by 50% as compared to level-1.